Assessment of Government Health Expenditure and Economic Growth in Kenya - Kelvin Mutira Misango; Dr. Richard Siele; Dr. Kipruto Kemboi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
Kenya's Vision projected an economic growth rate of 10 per cent per annum from 2008 to 2030 which has not been achieved to date. The purpose of this study was to assess the impact of Health Expenditure on economic growth in Kenya as one of the health indicator hindering growth rate. The study adopted the endogenous growth theory and incorporated key health expenditure into the model as a function of human capital. The research design employed was explanatory and relied on secondary data from World Bank from 1987 to 2018. Applying the regression model, the results revealed that the coefficient of healthcare expenditure was 0.3032, which was positive and insignificant at a 5 per cent level. This implied that for every one per cent increase in the coefficient of health care expenditure, the GDP growth rate could increase by 0.3032 %. The Kenya government could put in place health policies promoting citizens' health under social pillar and also increase allocation to health care to promote economic growth